Molecularly engineered PW12@Polypyrrole/MXene composite for high-energy, high-rate lithium-ion capacitor - Pawar, Meenakshi D.; Pandey, Priyanshi; Shelke, Manjusha (Journal of Energy Storage, 2026)
Due to inherent differences in the charge storage mechanisms of anode and cathode in a hybrid lithium-ion capacitor (LIC), a significant kinetic balance exists, necessitating the need to improve the ion/electron transfer capability of anode materials. In this study, we have developed a ternary pseudocapacitive composite comprising redox-active phosphotungstic acid nanoclusters (PW12) anchored to polypyrrole nanofibers (PPy), which are further decorated with Ti3C2Tx MXene (PW12@PPy/Ti3C2Tx) synthesized via an in-situ polymerization strategy. Here, Ti3C2Tx MXene serves as a conductive scaffold for PW12 wrapped PPy nanofibers, promoting efficient electron/ion transport. Simultaneously, the incorporation of PW12-anchored PPy nanofibers effectively mitigates the natural tendency of MXene to restack, thus preserving its layered structure. The PW12@PPy/Ti3C2Tx hybrid composite material delivers a high specific capacity of 767 mAh g-1 at 0.1 A g-1 after 100 cycles and a promising cycling stability of 280 mAh g-1 at 1 A g-1 up to 600 cycles. Moreover, an assembled LIC device using PW12@PPy/Ti3C2Tx as anode with nitrogen-doped sucrose carbon (NSC) as cathode demonstrates the highest energy density of 125 Wh kg-1 and maximum power density of 17,058 W kg-1. The device also maintains good cycling stability of 78.4 % capacity retention after 10,000 cycles at 1 A g-1. These results highlight a promising pathway for designing MXene-based hybrid composites with enhanced lithium storage performance, effectively addressing the kinetic mismatch challenges in LIC anode applications.
Keywords: Full cell device; Li ion diffusion; Lithium-ion capacitor; MXene; polyoxometalates; polypyrrole